The missing pieces of the euro architecture - Grégory Claeys (Bruegel, 2017)
This policy contribution describes the institutional flaws of the single currency revealed by the euro crisis and the institutional reforms that were put in place during and in the aftermath the crisis, and evaluates the remaining fragilities of the architecture of the European monetary union. In order to achieve a more resilient monetary union in Europe, we propose: 1) to form a 'financing union' through the completion of the banking union and the promotion of an ambitious capital markets union to provide private risk sharing between the countries of the monetary union; and 2) to improve the defective macroeconomic policy framework to avoid a repeat of the mistakes of recent years. The latter involves: reforming the European Stability Mechanism / Outright Monetary Transactions framework to clarify its functions and improve its governance system, reforming the European fiscal rules to make them more effective to achieve the two desirable objectives of sustainability and stabilisation, and creating a small-scale euro-area stabilisation tool to provide public risk sharing in case of significant shocks that members of the monetary union cannot deal with alone and to help manage the euro-area aggregate fiscal stance. A promising option to carry out these tasks would be to establish a European Unemployment Insurance Scheme. To ensure the democratic legitimacy of this overhauled euro-area governance framework, a European Fiscal Governing Council composed of six executive board members - including a euro-area finance minister - and of the finance ministers of the euro-area countries, would oversee the whole system and exercise the necessary discretion, while being accountable to the European Parliament in euro-area format.
Keywords: 330